High-performance magnesium-based thermoelectric materials: Progress and challenges - Zizhen Zhou; Guang Han; Xu Lu; Guoyu Wang; Xiaoyuan Zhou (Journal of Magnesium and Alloys, 2022)
Magnesium-based materials have been regarded as promising candidates for large-scale, high-efficiency thermoelectric applications, owing to their excellent dimensionless figure of merit, high abundance, and low cost. In this review, we comprehensively summarize the recent advances of Mg-based thermoelectrics, including Mg2X (X = Si, Ge, Sn), Mg3(Sb,Bi)2, and α-MgAgSb, from both material and device level. Their electrical and thermal transport properties are first elucidated based on the crystallographic characteristics, band structures, and phonon dispersions. We then review the optimization strategies towards higher thermoelectric performance, as well as the device applications of Mg-based thermoelectric materials and the related engineering issues. By highlighting the challenges and possible solutions in the end, this review intends to offer perspectives on the future research work to further enhance the performance of Mg-based materials for practical applications.